2017
DOI: 10.1038/s41598-017-17479-8
|View full text |Cite
|
Sign up to set email alerts
|

The highly efficient photocatalytic and light harvesting property of Ag-TiO2 with negative nano-holes structure inspired from cicada wings

Abstract: The negative replica of biomorphic TiO2 with nano-holes structure has been effectively fabricated directly from nano-nipple arrays structure of cicada wings by using a simple, low-cost and highly effective sol-gel ultrasonic method. The nano-holes array structure was well maintained after calcination in air at 500 °C. The Ag nanoparticles (10 nm–25 nm) were homogeneously decorated on the surface and to the side wall of nano-holes structure. It was observed that the biomorphic Ag-TiO2 showed remarkable photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Ag/TiO 2 displays distinct diffraction peaks at 2θ = 25.8°, 37.8°, 48.1°, and 55.2°, which indicate the typical anatase phase of TiO 2 (Cao et al, ). The diffraction peaks of Ag are not obvious, it may be attributed to the low loaded content of Ag nanocrystals, and the (111) plane of Ag (2θ = 37.8°) overlaps with the diffraction peaks of the TiO 2 (004) plane (Lian et al, ; Zada et al, ). The peaks of TiO 2 were not disturbed by Ag, and the lack of change indicated that Ag did not enter the lattice of TiO 2 (Zada et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ag/TiO 2 displays distinct diffraction peaks at 2θ = 25.8°, 37.8°, 48.1°, and 55.2°, which indicate the typical anatase phase of TiO 2 (Cao et al, ). The diffraction peaks of Ag are not obvious, it may be attributed to the low loaded content of Ag nanocrystals, and the (111) plane of Ag (2θ = 37.8°) overlaps with the diffraction peaks of the TiO 2 (004) plane (Lian et al, ; Zada et al, ). The peaks of TiO 2 were not disturbed by Ag, and the lack of change indicated that Ag did not enter the lattice of TiO 2 (Zada et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peaks of Ag are not obvious, it may be attributed to the low loaded content of Ag nanocrystals, and the (111) plane of Ag (2θ = 37.8°) overlaps with the diffraction peaks of the TiO 2 (004) plane (Lian et al, ; Zada et al, ). The peaks of TiO 2 were not disturbed by Ag, and the lack of change indicated that Ag did not enter the lattice of TiO 2 (Zada et al, ). The UV–Vis spectrum of the Ag/TiO 2 photocatalysts is shown in Figure b; D‐TiO 2 showed slightly higher absorbance than Ag/TiO 2 in the UV light region, which might be due to the abundance of TiO 2 (Zhang, Zhou, Bao, Zhang, & Sheng, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods such as replica molding or etching allow functional surface topography to be transferred to relevant surfaces where their beneficial properties can be studied [22][23][24][25]. The molding of surfaces that are covered in nano-and micron-scale features has already been achieved using various techniques such as soft lithography, photolithography, injection molding, hot embossing, atomic layer deposition, capillary force lithography and ultraviolet nanoimprint lithography (NIL) [26][27][28][29][30][31][32][33][34][35]. Depending on the molding polymer and technique employed, feature resolutions of 100 nm can be achieved, with reports of features as small as 6 nm in diameter [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…However, bare TiO 2 suffers from low efficiency and narrow light-response range which restrict its application in solar light photocatalysis 2123 . Furthermore, the agglomeration of TiO 2 nanoparticles could significantly decrease their photocatalytic activity, and highly-dispersed TiO 2 nanoparticles are desirable.…”
Section: Introductionmentioning
confidence: 99%